Risk factors associated with intraventricular hemorrhage in extremely premature neonates. Issue 1 (January 2018) - Roberts, Jonathan C.; Javed, M. Jawad; Hocker, James R.; Wang, Huaping; Tarantino, Michael D.
Abstract : N/A: Intraventricular hemorrhage (IVH) is a significant cause of morbidity in extremely premature infants despite many advances in neonatal intensive care. We conducted an institutional retrospective review aimed to correlate risk factors associated with IVH. Clinical variables reported to the Vermont-Oxford Network on less than 30 weeks gestational age infants over a 5-year period were evaluated with Pearson's chi-square and multivariate logistic regression. Of 618 infants born less than 30-week gestational age, 178 (28.8%) experienced IVH. Of those less than 1000 g, 105 (36.5%) of 288 infants experienced IVH. Multivariate analysis revealed that thrombocytopenia [odds ratio (OR) 2.03, 95% confidence interval (CI) 1.30–3.19, P = 0.0020] and cardiopulmonary resuscitation (CPR) ± intubation at delivery (OR 1.84, 95% CI 1.12–3.02, P = 0.0162) were independently associated with IVH. Among infants less than 1000 g, thrombocytopenia (OR 2.09, 95% CI 1.22–3.60, P = 0.0077) and CPR ± intubation at delivery (OR 2.01, 95% CI 1.10–3.68, P = 0.0229) were also significantly associated with IVH. IVH is a complex phenomenon with many contributing risk factors. In our study, infants less than 30-week gestational age and less than 1000 g revealed thrombocytopenia and CPR ± intubation in delivery room were independently associated with IVH. These data should alert clinicians to those neonates most likely to suffer IVH.